Interleukin-9 Deletion Relieves Vascular Dysfunction and Decreases Blood Pressure via the STAT3 Pathway in Angiotensin II-Treated Mice - Yunzhao Yang; Shaoqun Tang; Chunchun Zhai; Xin Zeng; Qingjian Liu; Cheng Xu; Hexiang Chen (Mediators of Inflammation)
Background. Multiple interleukin (IL) family members were reported to be closely related to hypertension. We aimed to investigate whether IL-9 affects angiotensin II- (Ang II-) induced hypertension in mice. Methods. Mice were treated with Ang II, and IL-9 expression was determined. In addition, effects of IL-9 knockout (KO) on blood pressure were observed in Ang II-infused mice. To determine whether the effects of IL-9 on blood pressure was mediated by the signal transducer and activator of the transcription 3 (STAT3) pathway, Ang II-treated mice were given S31-201. Furthermore, circulating IL-9 levels in patients with hypertension were measured. Results. Ang II treatment increased serum and aortic IL-9 expression in a dose-dependent manner; IL-9 levels were the highest in the second week and continued to remain high into the fourth week after the treatment. IL-9 KO downregulated proinflammatory cytokine expression, whereas it upregulated anti-inflammatory cytokine levels, relieved vascular dysfunction, and decreased blood pressure in Ang II-infused mice. IL-9 also reduced smooth muscle 22α (SM22α) expression and increased osteopontin (OPN) levels both in mice and in vitro. The effects of IL-9 KO on blood pressure and inflammatory response were significantly reduced by S31-201 treatment. Circulating IL-9 levels were significantly increased in patients with the hypertension group than in the control group, and elevated IL-9 levels positively correlated with both systolic blood pressure and diastolic blood pressure in patients with hypertension. Conclusions. IL-9 KO alleviates inflammatory response, prevents phenotypic transformation of smooth muscle, reduces vascular dysfunction, and lowers blood pressure via the STAT3 pathway in Ang II-infused mice. IL-9 might be a novel target for the treatment and prevention of clinical hypertension.